Analysis of outcomes for communication mode in cochlear implant in prelingually deafened adults. Issue 2 (April 2023) - Oyamada, Shogo; Takahashi, Masahiro; Furutate, Sakiko; Oka, Shinichirou; Kubota, Eri; Sakurai, Azusa; Uekusa, Tomoko; Iwasaki, Satoshi
Abstract: Objective: Recent studies have suggested that speech perception outcomes after cochlear implantation (CI) in prelingually deafened adults have improved with advances in CI technology and speech processing strategies. However, the outcomes vary from case to case. Communication mode has been reported in many studies as the factor that related to the post CI outcomes. This study aimed at investigating the post CI outcomes and the progress during 2 years for each communication mode. Material and Methods: The subjects were 17 prelingually deafened adults undergoing CI at our hospital between April 2013 and March 2019. We investigated preoperative factors affecting post CI outcomes. Also we analyzed post CI outcomes for each communication mode and compared preoperative factors for each communication mode. Results: Communication mode and preoperative discrimination score were the factor affecting on postoperative discrimination score. The speech perception score after CI improved significantly in the oral and lip-reading group and total communication group. The speech perception scores in postlingually deafened adults improved significantly during the first six months and became to plateau after CI. On the other hand, the scores of prelingually deafened adults tended to improve gradually after six months postoperatively. Furthermore, the degree of improvement and progress differed by each communication mode. Conclusion: The communication mode is important factors in predicting outcomes in prelingually deafened adults after CI. Long-term auditory training is important for prelingually deafened adults who use visual information as their preoperative method of communication.